Contract farming and the state - Sukhpal Singh (Delhi, 2006)
This book examines the contract farming systems in Thailand and India with focus on the role of the state in the two countries. Contract farming in Thailand makes an interesting and important study as it has been promoted by the Thai state actively and the country has been a pioneer in this regard in South-East Asia. Now, contract farming is becoming popular in rest of the South-East and the Asian region including India where in many countries, state is encouraging it. Therefore, a study of contract farming system in Thailand which is considered to be a relative success is both crucial and timely. The present study is based on case studies of four agribusiness firms and their farmers in northern Thailand in potato and sweet corn crops, after an exhaustive survey and review of literature focusing on the spread and performance of contract farming in Thailand and the role of the state in it. These case studies focus on firm-farmer relationship and their perceptions about working of the contract system. After giving a conceptual and theoretical understanding of the contract farming system, the book goes on to give the rationale for examining the contract farming system in Thailand and India. It addresses as an important issue the role of the state in promotion of contract farming system in Thailand and India as the former has had a very formal intervention in this regard under the four sector co-operation plan, though it has not been seriously studied by researchers until now, and the latter has started intervening more recently. The study also attempts to look at the larger impacts of contracting on the local economy in the two countries. Finally, the book draws inferences about leveraging contract farming for agricultural development in India based on the Thai and the Indian experiences.
Keywords: Contract farming-India